Hubungan Frekuensi Bangkitan dengan Skor Kualitas Hidup pada Penderita Epilepsi Umum di RSUD Dr. Moewardi - Fillisita Chandramalina Dewayani; Diah Kurnia Mirawati; Endang Sutisna Sulaeman (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Epilepsy is a chronic neurology disease. When epilepsy was not well-controlled, it could cause so many effects such as decreasing quality of life score. The aim of this study was to find out the relation between seizure frequency and quality of life score of general epileptic patients in Dr. Moewardi hospital. Methods: This was an observational study with analytic cross-sectional approach conducted from July to August 2012 at Neurology Department of Dr. Moewardi hospital. Samples were taken by purposive sampling after selected based on inclusion and exclusion criteria. The frequency of seizure was recorded by medical record. The quality of life was assessed by QOLIE-31 questionnaire. Score of seizure frequency and quality of life were analyzed with one-way ANOVA models by SPSS 17.0 for Windows. Results: There were 30 samples consist of 13 women and 17 men. The average of quality of life total score in high seizure frequency was 59.56 4.71, medium seizure frequency was 78.32 2.20, and seizure free was 83.40 2.34. There was a negative relationship between seizure frequency and quality of life score on patients with general epilepsy. Analysis by one-way ANOVA/Kruskal Wallis showed a statistically significant relationship (p < 0.05) for total score component and the other seven components. Conclusion: Patients with higher seizure frequency had lower quality of life score. Keywords: seizure frequency, quality of life score, general epilepsy